Global discovery of high-NaCl-induced changes of protein phosphorylation - Wang, Rong (American Physiological Society, 2014)
High extracellular NaCl, such as in the renal medulla, can perturb and even kill cells, but cells mount protective responses that enable them to survive and function. Many high-NaCl-induced perturbations and protective responses are known, but the signaling pathways involved are less clear. Change in protein phosphorylation is a common mode of cell signaling, but there was no unbiased survey of protein phosphorylation in response to high NaCl. We used stable isotopic labeling of amino acids in cell culture coupled to mass spectrometry to identify changes in protein phosphorylation in human embryonic kidney (HEK 293) cells exposed to high NaCl. We reproducibly identify >8,000 unique phosphopeptides in 4 biological replicate samples with a 1% false discovery rate. High NaCl significantly changed phosphorylation of 253 proteins. Western analysis and targeted ion selection mass spectrometry confirm a representative sample of the phosphorylation events. We analyze the affected proteins by functional category to infer how altered protein phosphorylation might signal cellular responses to high NaCl, including alteration of cell cycle, cyto/nucleoskeletal organization, DNA double-strand breaks, transcription, proteostasis, metabolism of mRNA, and cell death.